Harmonisasi Kuantum Islam dalam Pendidikan Islam: Perspektif Islam Melalui Lensa Filsafat Nidhal Guessoum - shobiha, shobihatul fitroh noviyanti; Mahfudloh, Ririn Inayatul; Romzi, Moh (Jurnal Studi Multidisiplin Qomaruna, 2024)
The purpose of this writing is to discuss Nidhal Guessoum's study of his thoughts, namely the correlation between Islam and modern science. The explanation is about cosmology, from classical (medieval) Islamic philosophy, scientific interpretation, traditionalism, and modern science from various points of view of Muslim thinkers. This article, which uses a literature study using a qualitative approach, discusses Nidhal Guessoum's thoughts on Islam and modern science. The idea of Islamic/theistic cosmology put forward by Nidhal is the result of his opinion. Cosmology is used as a circle in the frame of monotheism. His opinion on scientific issues such as cosmology cannot be answered by science, but requires a Muslim with his identity to study science while still believing in the existence of God. According to Nidhal, the emphasis of Islamic cosmology should not only be in the form of scientific interpretation or scientific interpretation as has been embodied by some munfasir. Nidhal's alternative as an offer to ideas that apparently contain weaknesses and cannot be developed is the quantum approach. The quantum approach is based on three principles to be an integration of religion with modern science